The Ubiquitin Proteasome System in Periodontal Disease: A Comprehensive Review - Machado, Vanessa; Carvalho, Rui; Mendes, José João; Botelho, João (Frontiers in Dental Medicine, 2020)
The turnover of intracellular proteins is a highly selective and regulated process. This process is responsible for avoiding injury and irreparable breakdown of cellular constituents. Its impairment disrupts cellular stability, integrity and homeostasis. The ubiquitin-proteasome system (UPS) is responsible for this programmed degradation of most intracellular proteins. This process involves a cascade of enzymes that involves the ubiquitin conjugation to a target substrate protein, its recognition and degradation by the proteasome. The turn-over of intracellular proteins is a non-stop ubiquitous process that regulates a series of mechanisms, for instance transcription, translation, endocytosis. In addition, proteasome act by releasing peptides that may serve to other purposes, such as antigen presentation in immune actions and enzymatic flagging towards biosynthesis and gluconeogenesis. The role of the UPS impairment in periodontal diseases is gaining growing. This acquaintance might contribute to the development of novel therapeutic applications. Thus, this review focuses on the latest progresses on the role of the UPS and its signaling pathways in Periodontal Medicine. Furthermore, we discuss the potential of UPS-based drugs development to be used in periodontal disease therapy.